Resilience of informal family caregivers of elderly dependents - Mateus, Maria Nascimento (2019)
The study, aims to understand the adaptive capacity of informal family caregivers (IFC), faced with the difficulties experienced daily, through the concept of resilience. Research the problem - What is the resiliency capacity of IFC of dependent elderly, given the difficulties resulting from caring? Are defined the objectives: to understand the difficulties associated with the act of caring, check the constraints felt in the personal life of IFC, evaluate the level of resilience of the IFC. The methodology was quantitative and qualitative, and a questionnaire survey was used as a data collection instrument, a semi-structured interview, and the application of the Resilient Coping Brief Scale. The sample was selected for convenience, 20 IFC, 10 of de rural environment an 10 of urban environment. The results show a higher resilience when their sons are the caregivers. The difficulties are related to the physical and emotional / psychological exhaustion, the limitation of freedom and the alteration of the family dynamics the great constraints in personal life.